2016
DOI: 10.1515/sjecr-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Complexes with Edda (Ethylenediamine -N, N - Diacetate) Ligands as Potential Anticancer Agents

Abstract: e design of platinum based drugs is not a new fi eld of interest. Platinum complexes are widely used as anticancer agents and currently, approximately 30 platinum(II) and platinum(IV) entered into some of the phases of clinical trials. A special place in today's research belongs to platinum complexes with diammine ligands. A large number of edda (ethylenediamine-N, N'-diacetate)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…The tested compounds show stronger activity in higher doses and long‐term exposure periods; however, they caused a significant reduction in the viability of the nonmalignant tested cell line. Interestingly, time and dose dependence were observed for all investigated compounds, but dependence on chain length was not detected as it was noted previously for platinum complexes with edda (ethylenediamine‐ N , N′ ‐diacetate) ligands by Jurišević et al (2016). Dimitrijević et al (2013) also reported that these compounds were much more potent than cisplatin, by evaluating their cytotoxic capacity on CLL (freshly isolated chronic lymphocytic leukemia cells).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The tested compounds show stronger activity in higher doses and long‐term exposure periods; however, they caused a significant reduction in the viability of the nonmalignant tested cell line. Interestingly, time and dose dependence were observed for all investigated compounds, but dependence on chain length was not detected as it was noted previously for platinum complexes with edda (ethylenediamine‐ N , N′ ‐diacetate) ligands by Jurišević et al (2016). Dimitrijević et al (2013) also reported that these compounds were much more potent than cisplatin, by evaluating their cytotoxic capacity on CLL (freshly isolated chronic lymphocytic leukemia cells).…”
Section: Discussionsupporting
confidence: 71%
“…Until now, about 30 new compounds entered some phase of the clinical trial. Yet, only a few have been introduced into clinical practice (Gibson, 2019; Jurišević et al, 2016; Petrović et al, 2020). Among others, Pt complexes with diamine ligands are in the field of interest as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large number of edda (ethylenediamine- N,N’ -diacetate)-type ligands and their corresponding platinum complexes have been successfully synthesized [ 11 , 12 ] and some of them showed significant cytotoxic effects [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…17,20 It was found that generally they are less efficient than cisplatin. Opposite them, Pt IV complexes with esterifies edda-type ligands showed greater anticancer activity than corresponding Pt II complexes and cisplatin, [21][22][23] causing very rapid necrotic cell death in some cell lines.…”
Section: Introductionmentioning
confidence: 99%